2013
DOI: 10.1111/j.1600-6143.2012.04334.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Everolimus Versus Mycophenolate Upon Proteinuria Following Kidney Transplant and Relationship to Graft Outcomes

Abstract: Although mTOR inhibitor use has been associated with proteinuria in kidney transplant recipients, dose dependency and impact on allograft function are unknown. In a post hoc analysis, we compared rates of proteinuria 3 months posttransplant among everolimus (EVR) and mycophenolate (MPA) treatment arms and used a time-dependent model to correlate the risk of proteinuria to EVR trough levels up to 24 months posttransplant. eGFR and graft loss was compared by proteinuria status at 3 months. Of 833 randomized pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 22 publications
(19 reference statements)
0
15
1
Order By: Relevance
“…A recent study by Wiseman et al 45 suggests a dose dependent effect of everolimus on proteinuria. In this randomized trial 277 patients received 1.5 mg/day of everolimus, 279 received 3 mg/day of everolimus, and 277 received mycophenolic acid (MPA).…”
Section: Risk Factors and Causes For Proteinuriamentioning
confidence: 97%
“…A recent study by Wiseman et al 45 suggests a dose dependent effect of everolimus on proteinuria. In this randomized trial 277 patients received 1.5 mg/day of everolimus, 279 received 3 mg/day of everolimus, and 277 received mycophenolic acid (MPA).…”
Section: Risk Factors and Causes For Proteinuriamentioning
confidence: 97%
“…Evidence from several studies has demonstrated that risk factors associated with the development of proteinuria include higher EVR concentrations [19]. Moreover, proteinuria is more common in patients who were converted from CNI to mTOR-based immunosuppressive regimen [20,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Although specific causes of death and graft loss have not been studied systematically, adverse events typically associated with the use of imTORs such as proteinuria, [22][23][24] diabetes mellitus after transplantation [25][26][27] and dyslipidemia 27 may be involved in these findings. These complications, however, are associated with the relatively high blood concentrations of iCN and imTOR initially used.…”
Section: Critical Analysis Of Mortality Studies and Graft Losses Withmentioning
confidence: 99%